MACROECONOMIC IMBALANCE AND FORMS OF ITS MANIFESTATION IN ECONOMY - Oleksandr Dmytrenko; Artem Bulik (Соціальна економіка, 2019)
The purpose of the article is to systematize the effects of changes in the external and internal macroeconomic environment and to analyze the scientific possibilities of their further theoretical development. Permanent relevance of the study of equilibrium states in the economy is conditioned by the development of forms of organization of economic relations and changes in the socio-economic environment of their realization. This problem is of particular relevance in the context of the global financial crisis, which is characterized by a deviation of basic macroeconomic indicators from their equilibrium values. The study showed that the influence of price factors on the balance of supply and demand in all major markets of Ukraine's economy and, above all, in the market of final products and services, has increased. Analytical assessment of the influence of individual price factors on the dynamics of aggregate supply and demand has allowed to determine the features of this influence in the current conditions, characteristic for the economy of Ukraine, in particular, that the high level of export orientation of the industry and a significant dependence of final consumption on imports contribute to the dominance of the influence of external factors market of final goods and services. Among these factors, the most influential was the exchange rate. At the same time, one of the important factors of inflation is the dynamics of individual average costs as the main factor shaping producer prices. The economy of Ukraine is resource intensive, which is the result of an imperfect structure of production, burdened with capital and raw material production centers, and outdated technologies. And this is the main obstacle to the effective adaptation of Ukrainian producers' supply to changes in aggregate demand. The economic situation in Ukraine in 2014-2018 and in the short term is mainly determined by political factors, the further development of economic processes is largely unpredictable and will be determined primarily by whether the fighting will cease.